Silver coating on dental implant-abutment connection screws as potential strategy to prevent loosening and minimizing bacteria adhesion - Velasco-Ortega, Eugenio; Jiménez-Guerra, Alvaro; Ortiz-Garcia, Iván; Nuñez-Márquez, Enrique; Moreno-Muñoz, Jesús; Gil, Javier; Delgado, Luis M.; Rondón-Romero, José Luis; Monsalve-Guil, Loreto (Frontiers in Bioengineering and Biotechnology, 2024)
One of the main problems for the long-term behavior of dental implants are loosening of the implant-abutment connection screws and bacterial infiltration. The aim of this work is to increase the screw fixation by silver coating, providing superior mechanical retaining and antibacterial effect. Eighty dental implants with their abutments and screws have been studied. Twenty screws were not coated and were used as a control while the rest of screws were silver coated by sputtering, with three different thickness: 10, 20 and 40 µm and 20 screws per each thickness. Coating morphology and thickness were determined by scanning electron microscopy using image analysis systems. The screws were tightened for each of the thicknesses and the control with two torques 15 Ncm and 20 Ncm and tested under mechanical fatigue simulating oral stresses up to a maximum of 500,000 cycles. The remaining torques at different cycles were determined with a high-sensitivity torquemeter. Cell viability assays were performed with SaOs-2 osteoblasts and microbiological studies were performed against Streptococcus gordonii and Enterococcus faecalis bacteria strains, determining their metabolic activity and viability using live/dead staining. It was observed a decrease in torque as cycles increase. For a preload of 15 Ncm at 100,000 cycles, the loosening was complete and, for 20 Ncm at 500,000 cycles, 85% of torque was lost. The silver coatings retained the torque, especially the one with a thickness of 40 µm, retaining 90% of the initial torque at 500,000 cycles. It was observed that osteoblastic viability values did not reach 70%, which could indicate a slight cytotoxic effect in contact with cells or tissues; however, the screw should not be in direct contact with tissue or living cells. Silver coating induced a significant reduction of the bacteria metabolic activity for Streptococcus gordonii and Enterococcus faecalis, around 90 and 85% respectively. Therefore, this coating may be of interest to prevent loosening of implant systems with a worthy antibacterial response.